Long-term stable hydrogen production from acetate using immobilized Rhodobacter capsulatus in a panel photobioreactor. (12th July 2019) - Elkahlout, Kamal; Sagir, Emrah; Alipour, Siamak; Koku, Harun; Gunduz, Ufuk; Eroglu, Inci; Yucel, Meral
Abstract: Biological hydrogen production is attractive since renewable resources are utilized for hydrogen production. In this study, a novel panel photobioreactor (1.4 L) was constructed from Plexiglas with a network of nylon fabric support for agar immobilized bacteria complex. Two strains of Rhodobacter capsulatus DSM 1710 wild-type strain and Rhodobacter capsulatus YO3 (hup −, uptake hydrogenase deleted mutant) with cell concentrations of 2.5 and 5.0 mg dcw/mL agar, respectively were entrapped by 4% (w/v) of agar. The system was operated for 72–82 days in a sequential batch mode utilizing acetate as substrate at 30 °C under continuous illumination. Immobilization increased the stability of the photobioreactors by reducing the fluctuations in pH. The pH remained between 6.7 and 8.0 during the process. Both hydrogen yield and productivity were higher in immobilized photobioreactors compared to suspended culture. The highest hydrogen productivities of 0.75 mmol H2 /L/h and 1.3 mmol H2 /L/h were obtained by R. capsulatus DSM1710 and R. capsulatus YO3 respectively. Highlights: Biological hydrogen from acetate by agar immobilized Rhodobacter capsulatus. Long-term hydrogen production for 72–82 days in indoors. The range of pH change was between 6.7 and 8.0 throughout the process. The highest productivity of 1.3 mmol H2 /L/h was obtained by R. capsulatus YO3. The highest hydrogen yield was 3.53 mol H2 /mol acetate by R. capsulatus YO3.